2014
DOI: 10.1002/dvdy.24173
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid, a histone deacetylase inhibitor, regulates cell proliferation in the adult zebrafish optic tectum

Abstract: Background: Valproic acid (VPA) has been used to treat epilepsy and bipolar disorder. Several reports have demonstrated that VPA functions as a histone deacetylase (HDAC) inhibitor. While VPA is known to cause teratogenic changes in the embryonic zebrafish brain, its effects on neural stem cells (NSCs) in both the embryonic and adult zebrafish are not well understood. Results: In this study, we observed a proliferative effect of VPA on NSCs in the embryonic hindbrain. In contrast, VPA reduced cell proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 47 publications
(78 reference statements)
1
24
0
1
Order By: Relevance
“…However, the molecular mechanisms underlying NSC proliferation and differentiation are largely unknown. We have shown that Notch signaling regulates NSC proliferation (Dozawa et al, 2014); we also observed the gene expression of other signalingrelated molecules known to be involved in NSC proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 70%
“…However, the molecular mechanisms underlying NSC proliferation and differentiation are largely unknown. We have shown that Notch signaling regulates NSC proliferation (Dozawa et al, 2014); we also observed the gene expression of other signalingrelated molecules known to be involved in NSC proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 70%
“…It has been well established that HDAC inhibitors decrease the proliferation of NSCs (Dozawa et al., 2014). We further determined whether the mTOR pathway mediated the effect of VPA on the proliferation of NSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Notch signaling has also been reported to regulate RG proliferation after stab injury in the telencephalon (Kishimoto, Shimizu, & Sawamoto, 2012). In the optic tectum, Notch signaling related genes such as notch and delta family genes and bHLH transcriptional factors her4 and her6 are expressed, and Notch signaling regulates the proliferation of NE (Chapouton et al, 2011;de Oliveira-Carlos, Ganz, Hans, Kaslin, & Brand, 2013;Dozawa et al, 2014). We analyzed the expression levels of her4 and her6 in the optic tectum after stab injury and analyzed the effects of Notch inhibition on RG proliferation and differentiation into neurons after stab injury.…”
mentioning
confidence: 99%